2007
DOI: 10.1038/sj.ejhg.5201934
|View full text |Cite
|
Sign up to set email alerts
|

Y-chromosome diversity characterizes the Gulf of Oman

Abstract: Arabia has served as a strategic crossroads for human disseminations, providing a natural connection between the distant populations of China and India in the east to the western civilizations along the Mediterranean. To explore this region's critical role in the migratory episodes leaving Africa to Eurasia and back, high-resolution Y-chromosome analysis of males from the United Arab Emirates (164), Qatar (72) and Yemen (62)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 58 publications
6
92
0
Order By: Relevance
“…All chromosomes unresolved previously beyond the R1-M173* level 14,15,35,36 that were available to us are now attributed to either R1a*-M420 or R1b*-M343 haplogroups. Consequently, we revise the haplogroup nomenclature following the YCC guidelines.…”
Section: Resultsmentioning
confidence: 84%
“…All chromosomes unresolved previously beyond the R1-M173* level 14,15,35,36 that were available to us are now attributed to either R1a*-M420 or R1b*-M343 haplogroups. Consequently, we revise the haplogroup nomenclature following the YCC guidelines.…”
Section: Resultsmentioning
confidence: 84%
“…Although J1e is one of the most frequent haplogroups in the region, haplogroup E-M123 also shows its highest frequency and haplotype diversity in regions of the Fertile Crescent, decreasing toward the Arabian Peninsula. 1,2,6 This co-distribution pattern of Y-chromosome haplogroups J1e and E-M123 resembles mtDNA haplogroups J1b and (PreHV)1 distributions that also display low levels of diversity despite their high frequency in Saudi Arabia. 32,33 Although on a broad scale the haplogroup J1e frequency distribution and expansion times are consistent with the model that it tracks a possible expansion of Neolithic agro-pastoralists from the Fertile Crescent into the arid Arabian Peninsula, several caveats must be considered.…”
Section: Resultsmentioning
confidence: 79%
“…This haplogroup essentially bifurcates into two main subclades, J1-M267 and J2-M172. 1 Previous studies of J1-M267 [2][3][4][5][6][7] have found it to occur at high frequencies among the Arabic-speaking populations of the Middle East, conventionally interpreted as reflecting the spread of Islam in the first millennium CE. 8 However, before the middle first millennium CE, a variety of Semitic languages were spoken throughout the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…We assembled a genotyping panel of 16 244 males from 126 Eurasian populations, some of which we report upon for the first time herein and others that we have combined from earlier studies, 22,[29][30][32][33][34][35][36][37][38][39][40][41][42][43][44][45] and updated to a higher level of phylogenetic resolution. All samples were obtained using locally approved informed consent and were de-identified.…”
Section: Population Samplesmentioning
confidence: 99%